PELAKSANAAN RUJUKAN PERSALINAN DAN KENDALA YANG DIHADAPI - Indarwati -; Wahyuni - (Universitas Duta Bangsa Surakarta, 2014)
Introduction; The result ofintroduction there are some difficulties referring to patients, such as family misunderstanding, patient’s fear of caesarean operation and financial problem for hospital that costly expense. Objective ; this study is to examine the ability of midwives to carry out the patient referral, The target to be achieved is to get a real picture whether its implementation is appropriate to BAKSOKU standard or not. Methods; Qualitative research in the form of phenomenological approach.in-depth interviewing with midwives who had referred patients childbirth, and triangulation was done by a chairman of IBI, between thehead of Child and Maternal Health Department and several midwives who accept the patient’s referral in hospitals. Result shows the majority of midwives have not implemented the patient referral according to BAKSOKU standard and midwives assistance during referring mostlymade only for significant conditions.. Finally, midwives difficult to find proper transportation for patients who live in the suburbs. Conclusion : the majority of midwives have not implemented the patient referral according to BAKSOKU standard and midwives assistance during referring mostlymade only for significant conditions.Key words: Maternal ,Refferral